Creative writing - Hamand, Maggie (Hoboken, New Jersey : John Wiley & Sons, Inc., 2023)
Unlock your creative potential and write something special. Ever dream of writing a book, article, poem, or play that means something to you$1 (Band maybe to someone else as well? Do you have an idea you're ready to get down on paper? In Creative Writing For Dummies, you'll learn how to unleash your creative side and become a confident and productive writer. Discover the essential elements of storytelling, including structure, characterization, setting, dialogue, and plot, as you navigate the countless ways you can express yourself with the written word. s
INTRODUCTION -- PART 1: GETTING STARTED -- CHAPTER 1: You and Your Writing -- CHAPTER 2: Getting into the Write Mindset -- CHAPTER 3: Finding Material to Work With -- PART 2: INTRODUCING THE ELEMENTS OF CREATIVE WRITING -- CHAPTER 4: Creating Characters -- CHAPTER 5: Giving Characters a Voice with Dialogue -- CHAPTER 6: Choosing a Narrator -- CHAPTER 7: Describing Your World -- CHAPTER 8: Plotting Your Way -- CHAPTER 9: Setting Up a Solid Structure -- CHAPTER 10: From Drafting to Rewriting and Editing: Making Your Work Shine -- PART 3: WRITING FICTION -- CHAPTER 11: When Less is More: Crafting Short Stories -- CHAPTER 12: Writing the Novel -- CHAPTER 13: Once Upon a Time: Writing for Children -- CHAPTER 14: Penning Plays -- CHAPTER 15: Writing Screenplays -- CHAPTER 16: Rhymes and Reasons: Writing Poetry -- PART 4: EXPLORING NONFICTION -- CHAPTER 17: Breaking into Journalism -- CHAPTER 18: Writing from Life: Giving a Voice to the Past -- CHAPTER 19: Crafting Narrative Nonfiction -- CHAPTER 20: Travel Writing: Tales for Armchair Explorers -- CHAPTER 21: All About Blogging -- PART 5: FINDING AN AUDIENCE -- CHAPTER 22: Finding Professionals to Publish Your Book -- CHAPTER 23: Staying in Control with Self-Publishing -- CHAPTER 24: Becoming a Professional -- PART 6: THE PART OF TENS -- CHAPTER 25: Ten Top Tips for Writers -- CHAPTER 26: Ten Ways to Get Noticed -- INDEX.
Includes index.
Keywords: CREATIVE WRITING; AUTHORSHIP